Hubungan Customer Relationship Management dengan Loyalitas Nasabah (Studi Kasus: PT Bank XYZ Cabang Bogor) - Reni Sanjaya; Ujang Sumarwan; - Kirbrandoko (Institut Pertanian Bogor, 2015)
Purpose of this study is to analyze the relationship between customer relationship management (CRM) which is measured through customer perception with the level of customer loyalty. The models used in this study are recency, frequency and monetary (RFM) that measures loyalty and CRM through people, process and technology. The analysis used is descriptive analysis, correspondence analysis, chi-square analysis and regression analysis. The data used are primary and secondary data. Primary data were collected with a structured interview based on the Likert scale. The population in this study is using purposive sampling, the customers of tabungan SiAga with nominal savings Rp25 million up to <175 million as many as 100 people are taken by the census method. The analyses of CRM the people variable with the indicators consist of enthusiasm, friendliness and ability; the process variables measured by indicators of profile identification, communication, souvenirs, and handling customer complaints and customized; the technology variable which indicators consist of customer database and communication media. While RFM analysis is measured by variables Recency, Frequency and Monetary. Based on segmentation RFM there are five segments; the segments are platinum segment, gold segment, silver segment, blue segment and black segment. The study states that the majority of tabungan SiAga XYZ costumers are in the silver segment (57 percent) with a high degree of recency; while the frequency and monetary aspects tends to be low, while for customers with a level of RFM that are high (platinum segment) about 12 percent. Meanwhile perception of the customers about CRM by Bank XYZ based on people, process and technology produce that the highest perception is in conformity of the customer database (technological aspects). However, customers have not been using the technological facilities and yet feel about the ease of transaction with technology. Based on regression analysis between CRM and loyalty, aspect of the business processes most affect the frequency and monetary, and then followed with the technological aspects that affect monetary. For people aspect does not affect the high or low value of RFM. The more loyal customer, the higher perception about the Bank XYZ is seen from the aspect of people, process and technology